Precaratory Provision in Serbian Legal System With a View to Other Legal Systems - Vidić, Jelena Đ; Kovačević, Milica S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
When it comes to free acquisition, it is generally accepted that a person who gives a certain benefit to someone, can burden that same benefit with some kind of duty, within the limits set by the law. However, the previously said does not indicate that the purpose of the burden is to set the counteraction to free acquisition, nor it is related to the restriction of freedom of acquisition, but to allowed modifications. One of the aforementioned modifications is a precaratory provision, which, in addition to conditions and deadlines, has found its place in the Inheritance law. Its legal effect is reflected in the constitution of the burden to a person designated by the deceased person. The authors examine: the concept and the effects of the precaratory provision in terms of its fulfillment, as well as the consequences that occur when the precaratory provision is not fulfilled; who can be a subject when it comes to the precaratory provision, if there are any legaly binding corelations between them, what kind of consequences the aforementioned brings with it; as well as where lies boundary of precaratory provision in relation to similar institutes. Special attention has been paid to the national legislation, with the overview of the current provisions of the former republics of SFRY, Russia, Bulgaria, Austria and Germany, for the sake of comparative analysis.